Hypothyroidism as an unusual emerging initial clinical manifestation in systemic lupus erythematosus - H., Basavaraj; Amarkhed, Preeti; G., Srinivas Rao; Desai, Shivali (International Journal of Contemporary Pediatrics, 2025)
Systemic lupus erythematosus (SLE) is a multisystem autoimmune inflammatory disorder which may be associated with other auto immune disorders. studies found that thyroid abnormalities were common in SLE patients. Here we are reporting a case of an adolescent girl initially presented with features of hypothyroidism who was later presented with anorexia, joints pain, pain abdomen with malar rash and discoid rash and diagnosed as systemic lupus erythematosus. emphasizing the importance of recognizing overlapping autoimmune disorders in pediatric patients, and the importance of thyroid disease should be acknowledged in the treatment of SLE.